1992
DOI: 10.1136/gut.33.8.1071
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Saccharomyces cerevisiae in patients with Crohn's disease and their possible pathogenic importance.

Abstract: Initial attachment of the cariogenic Streptococcus mutans onto dental enamel is largely promoted by the adsorption of specific salivary proteins on enamel surface. Some phosphorylated salivary proteins were found to reduce S. mutans adhesion by competitively inhibiting the adsorption of S. mutans-binding salivary glycoproteins to hydroxyapatite (HA). The aim of this study was to develop antiadherence compounds for preventing dental biofilm development. We synthesized phosphorylated polyethylene glycol (PEG) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 17 publications
2
76
0
1
Order By: Relevance
“…Levels of serum antibodies against multiple strains of S. cerevisiae (baker's and brewer's yeast) were found to be significantly elevated in the serum of CD patients, but not serum of UC patients (McKenzie et al, 1990;Giaffer et al, 1992). This was initially proposed as potentially indicating hypersensitivity to dietary antigens in CD.…”
Section: Panca and Ascamentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of serum antibodies against multiple strains of S. cerevisiae (baker's and brewer's yeast) were found to be significantly elevated in the serum of CD patients, but not serum of UC patients (McKenzie et al, 1990;Giaffer et al, 1992). This was initially proposed as potentially indicating hypersensitivity to dietary antigens in CD.…”
Section: Panca and Ascamentioning
confidence: 99%
“…A number of reports show that CD and UC patients have increased titers of antibodies against E. coli, aerobes, anaerobes and even enteric bacterial pathogens, and that these antibodies are of both systemic and mucosal origin (Monteiro et al, 1971;Tabaqchali et al, 1978;Blaser et al, 1984;Macpherson et al, 1996). The previously discussed ASCA in CD patients probably reflect the same type of broad anti-microbial reactivity associated with IBD (McKenzie et al, 1990;Giaffer et al, 1992). More recently, novel gut bacterial antigens have been reported in association with IBD, including the Pseudomonas fluorescens-associated sequence I2, the outer membrane porin C of E. coli (OmpC), and bacterial flagellins, towards which CD patients develop significantly higher antibody titers than UC or control subjects (Sutton et al, 2000;Landers et al, 2002;Lodes et al, 2004).…”
Section: Enhanced Reactivity To Bacterial Antigens In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, both brewing and baking strains of S cerevisiae provoke an antibody response in CD, implicating dietary antigens in disease pathogenesis [4] . One group has noted higher ASCA IgG antibody levels in patients with small bowel Crohn's disease vs those with colonic disease [18] . This same study found high levels of ASCA IgG but not IgA in celiac disease, indistinguishable from levels seen in CD.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some of the familial studies have yielded conflicting data. For example, one group showed increased ASCA production in familial vs sporadic CD [7] , but others have shown equal or increased ASCA prevalence for sporadic CD [9,[16][17][18] . Thus, the case for an environmental etiology for ASCA has been articulated as well.…”
Section: Introductionmentioning
confidence: 99%